Smoking Among Youths in China - Hesketh, Therese (© American Journal of Public Health 2001, 2001)
Objectives. To inform a prevention strategy, this study determined the prevalence of and attitudes toward smoking among Chinese secondary school students. Methods. Self-completion questionnaires were administered to 13- to 18-year-olds attending school in Zhejiang Province, eastern China. Results. Of the 6674 respondents, 15.9% (25.7% of the boys, 5.4% of the girls) were ever smokers. Only 0.3% were regular smokers. Of the ever smokers, 41.9% had smoked before 10 years of age and 7.9% before 5 years of age. Parental smoking was the strongest predictor of smoking. Conclusions. The very low prevalence of regular smoking found in this age group suggests that prevention programs in school may be beneficial. Parents should be encouraged to adopt more responsible attitudes toward smoking in the home.